2023
DOI: 10.1097/mao.0000000000003743
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Modifying Antirheumatic Drugs in the Treatment of Autoimmune Inner Ear Disease: A Systematic Review and Meta-Analysis of Auditory and Vestibular Outcomes

Abstract: Objective: To answer the following question: In patients with primary autoimmune inner ear disease (AIED), (population) what impact do disease-modifying antirheumatic agents (DMARDs) (intervention) when compared with no treatment or corticosteroids (comparison) have on auditory and vestibular outcomes (outcome)? Study Design: Systematic review and meta-analysis. Data Sources: According to PRISMA guidelines, PubMed, Scopus, CINAHL, and Cochrane Library databases were searched from inception to March 10, 2022. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…In these studies, the diagnosis of auto-immune inner ear disease relied on clinical and audiological criteria without the use of 3D-FLAIR MRI. Other studies have shown that anti-TNFα molecules were efficient in the treatment of sudden hearing loss associated with systemic inflammatory disorders [ 13 , 14 , 15 ] and in a recent meta-analysis, anti-rheumatologic drugs appeared to be effective in the treatment of chronic vestibulo-cochlear disorders [ 16 ]. Significant improvements in the pure-tone average (PTA) and the speech recognition threshold (SRT) were observed.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the diagnosis of auto-immune inner ear disease relied on clinical and audiological criteria without the use of 3D-FLAIR MRI. Other studies have shown that anti-TNFα molecules were efficient in the treatment of sudden hearing loss associated with systemic inflammatory disorders [ 13 , 14 , 15 ] and in a recent meta-analysis, anti-rheumatologic drugs appeared to be effective in the treatment of chronic vestibulo-cochlear disorders [ 16 ]. Significant improvements in the pure-tone average (PTA) and the speech recognition threshold (SRT) were observed.…”
Section: Introductionmentioning
confidence: 99%